A Model of Influential Factors in Franchise Operations - Helder de Souza Aguiar; Marcos Roberto Luppe; Paulo Tromboni de Souza Nascimento (BBR: Brazilian Business Review)
The objective of this theoretical essay was to construct a model of those factors that might at any time have an influence on the operation of a franchise unit. In order to do so, we studied and assessed articles and books between 2014 and 2019 that contain aspects related to franchise operations; they were compiled in a way that had not hitherto been addressed by seminal authors. We analyzed 191 works, of which 71 form part of this study. Preparation of the model is relevant for stimulating conceptual discussion in this field of studies since it has not yet been clearly defined in academic literature. From choosing future franchisees to the daily operation of the unit, there are many factors that can influence the performance, survival, profitability and even the franchisee’s satisfaction with their unit. The model, therefore, serves as the basis for the management actions of franchise networks in monitoring the activities of their franchise units.